2017
DOI: 10.1002/ajmg.a.38577
|View full text |Cite
|
Sign up to set email alerts
|

Arthrogryposis and pterygia as lethal end manifestations of genetically defined congenital myopathies

Abstract: Arthrogryposis multiplex congenita affects approximately 1 in 3,000 individuals of different ethnic backgrounds and displays an equal incidence in males and females. The underlying mechanism for congenital contracture of the joints is decreased fetal movement during intrauterine development. This disorder is associated with over 400 medical conditions and 350 known genes that display considerable variability in phenotypic expression. In this report, four fetal or perinatal autopsy cases of arthrogryposis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…At the other end of the spectrum are severe cases with prenatal onset of severe hypotonia and joint contractures, and these patients often die in childhood. 16,19,20 Many of our patient's features were consistent with the severe form of SMALED2. However, until that time, only missense variants had been reported to cause disease.…”
supporting
confidence: 64%
See 3 more Smart Citations
“…At the other end of the spectrum are severe cases with prenatal onset of severe hypotonia and joint contractures, and these patients often die in childhood. 16,19,20 Many of our patient's features were consistent with the severe form of SMALED2. However, until that time, only missense variants had been reported to cause disease.…”
supporting
confidence: 64%
“…We only became convinced that p.(N546del) was pathogenic after identifying a 12‐year‐old girl with similar features who also harbored the de novo deletion. While our manuscript was in preparation, Trimouille et al reported a family with SMALED caused by in‐frame deletion in BICD2 , p.(K508del), establishing that single amino acid deletions can also cause disease …”
mentioning
confidence: 82%
See 2 more Smart Citations
“…AMC has been previously described as being independent of sex (Darin, Kimber, Kroksmark, & Tulinius, ; Hall, ; Laitinen & Hirvensalo, ; Navti et al, ), and although X‐linked types of AMC exist, they are rare and there is no trend for a sex ratio (Ahmed et al, ). Although AMC seems to affect individuals from different ethnicities, AMC has been reported as more common in certain ethnic groups, for instance several types only reported in the Middle East (Bayram et al, ; Shohat et al, ).…”
Section: Discussionmentioning
confidence: 99%